Worker well-being and quit intentions: is measuring job satisfaction enough? - Pelly, Diane (My University, 2023)
The links between worker well-being and quit intentions have been well researched. However, the vast majority of extant studies use just one measure, job satisfaction, to proxy for worker well-being as a whole, thus ignoring its documented multidimensionality. This paper examines whether this approach is justified. Using novel survey data, I compare the extent to which alternative well-being indicators (job satisfaction, affect, engagement and the satisfaction of basic psychological needs) individually, and jointly, explain variation in the quit intentions of 994 full-time workers. I find systematic differences in the personal and well-being profiles of workers who intend quitting and those who do not. Furthermore, well-being indicators explain four to nine times more variation in quit intentions than wages and hours combined. The engagement measure performs best, explaining 22.5% of variation in quit intentions. Employing a composite model (job satisfaction + affect + engagement) significantly increases explanatory power. My results suggest that the standard single-item job satisfaction measure may be good enough for organisations who merely wish to identify categories of workers who may be most at risk of quitting. For organisations seeking to develop proactive quit prevention strategies however, supplementing job satisfaction with other indicators such as engagement should increase explanatory power and yield valuable, potentially actionable, insights.
PUBLISHED
Investigates the links between alternative measures of worker well-being and quit intentions
Keywords: Job satisfaction; SURVEY RESEARCH; WORKER WELLBEING; WORKER WELLNESS; Work Engagement; Worker retention